Effect of various ionic strengths on the stabilities of metal mediated ternary complexes - Ramu, Sridarala; Ram Mohan, Yamajala (International Journal of Engineering and Technology, 2019)
The stabilities of 1:1:1 ligand-metal-ligand complexes investigated at different ionic strength (KNO3) in the presence of mixed solvent (water50%+dioxane50%) system at temperature 250 centigrade by pH metric titration method. In this investigation copper, nickel, zinc and cobalt used as metal ions, Beta-Hydroxy ketone and Benzotriazole derivatives acted as ligands. Data of present investigation showed that Cu formed more stable complexes; it is followed by Zn and Ni complexes.Co formed less stable complexes. The stabilities of these 1:1:1 ligand-metal-ligand complexes are measured by Δ log K values, Percentage of stacking and intra molecular equilibrium constants.Due to overlapping of –CH₂CH₃,2-methyl propyl and C6H5CH2- side chains of BHK ligands with aromatic ring of the BTAZ ligands these ligand-metal-ligand complexes attained extra stabilities. The values of Δ log K values for pair of (BHK-Alkyl)/ (BHK-Benzyl)-Metal (II)-(BTAZ-Alkyl-OH) and (BHK-Alkyl)/ (BHK-Benzyl)-Metal (II)-(BTAZ-Phenyl-OH) are alike. This indicates the side chain/aromatic ring of BHK is overlaying with the Benzotriazole ring, but not with the phenyl side chain/aromatic ring of the BTAZ ligand.